2005
DOI: 10.1038/sj.bmt.1705064
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated immune responses to influenza vaccination in healthy volunteers and allogeneic stem cell transplant recipients

Abstract: Summary:Influenza is one of the most common respiratory diseases in humans. The response to vaccination is frequently poor in immunosuppressed individuals. The aim of the present study was to develop an enzyme-linked immunospot (ELISPOT) assay for measuring of the specific T-cell response to influenza vaccination. In all, 18 healthy subjects and six stem cell transplantation (SCT) patients tested before and 4 weeks after influenza vaccination were included in the present study. Peripheral blood lymphocytes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 21 publications
4
22
1
Order By: Relevance
“…No data concerning the kinetics of the immune response to antigenic challenge were presented. A previous study by this group 8 had reported similar results in a smaller cohort of transplant patients. Similar results have also been reported by Engelhard et al 6 and Pauksen et al 7 Thus, it appears that the immune response of stem cell transplant patients generally does not return to an entirely normal state, even at times long after hematopoietic engraftment and supposed immune homeostasis has been achieved.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…No data concerning the kinetics of the immune response to antigenic challenge were presented. A previous study by this group 8 had reported similar results in a smaller cohort of transplant patients. Similar results have also been reported by Engelhard et al 6 and Pauksen et al 7 Thus, it appears that the immune response of stem cell transplant patients generally does not return to an entirely normal state, even at times long after hematopoietic engraftment and supposed immune homeostasis has been achieved.…”
Section: Introductionsupporting
confidence: 71%
“…Cells were then resuspended in 200 µL of PBS-5% FBS. All F c receptors were blocked using 10 µL (0.01mg/mL)ofmouseIgGfor5minutestoreduce spuriousantibodybinding.Cellsuspensionswerethen stained using the following antibody-flurochrome conjugates (all at 0.01 mg/mL): CD3-Horizon v450 and CD19 PerCP-Cy 5.5 (BD Biosciences), CD4-FITC,CD8-PE-Cy7andGr-1-PE.Cellswereanalyzed byFACSforsamplescollectedat-3, 3,6,8,11,14,18, 21, 27 and 33 days after immunization. All cell counts were obtained with the use of a Hemavet Analyzer (Drew Scientific, Dallas, TX).…”
Section: Facs Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular IFN-g production was detected by the means of flow cytometry and enzyme-linked immunospot (Elispot) assays. 17,18 Detection of intracellular IFN-g production by flow cytometry One million PBMCs in 100 ml of RPMI per staining condition were placed in 96-well U-bottom tissue culture plates. The cells were stimulated with CMV antigen AD-169 (BioSite, Stockholm, Sweden) at 1 mg/ml and with PepMix pp65 (JPT Peptide Technologies GmbH, Berlin, Germany) at 25 mg/ml and incubated for 18 h at 371C in 5% CO 2 .…”
Section: Study Patientsmentioning
confidence: 99%
“…16 In immunocompromised patients with cancer, there is convincing evidence that vaccination can be used safely. 17,18 Little is known, however, about the effect of vaccination on cell-mediated immune reactivity in cancer patients undergoing surgery. In order to address this issue we have, to the best of our knowledge, undertaken the first study to investigate the effect of vaccination on monocyte HLA-DR expression and lymphokine release in patients with an upper aerodigestive tract tumour undergoing surgery or conservative treatment.…”
Section: Spies M Kip a Lau Et Al Enhanced Hla-dr Expression Aftmentioning
confidence: 99%